Strategi Pembelajaran Kontekstual Berbasis Teori kognitif Piaget untuk Meningkatkan Pemahaman Siswa pada Mata Pelajaran Al-Qur’an Hadits - Ni’maturrohmah; Ahmad Naufal Dhiyaaulhaq; Habib Al Buchori; Ahmad Faisal; Bagus Mahardika (PT. Nawa Edukasi Nusantara, 2026)
This research focuses on improving students' skills in understanding the Quran and Hadith by implementing a contextually oriented learning strategy based on Piaget's cognitive theory. The methodology used involves library research, where information is gathered from various sources, including books, journals, and scientific articles. A contextual approach is believed to connect the material taught to students' real-life experiences and experiences, making learning easier to understand and apply in everyday life. The findings of this study indicate that the use of a contextual approach plays a positive role in improving students' understanding and motivation in the Quran and Hadith subject. Furthermore, this approach also contributes to improving students' abilities through a better understanding of the values contained in religious texts. By connecting religious teachings with everyday experiences, it is hoped that students can internalize Islamic values in their lives. The conclusion of this study confirms that the contextual approach is not only effective in improving the quality of Quran and Hadith learning but also very beneficial in supporting the goal of religious education to build student character in line with Islamic teachings.